1990
DOI: 10.1042/bj2700181
|View full text |Cite
|
Sign up to set email alerts
|

Localization of catalytic and regulatory subunits of cyclic AMP-dependent protein kinases in mitochondria from various rat tissues

Abstract: Observation and quantification of the catalytic subunit C of cyclic AMP-dependent protein kinases by immuno-gold electron microscopy suggested a high concentration of cyclic AMP-dependent protein kinases in mitochondria from liver, kidney, heart and skeletal muscle, pancreas, parotid gland and brain cells. The position of gold particles pointed to a localization in the inner membrane/matrix space. A similar distribution was obtained by immunolocalization of the cyclic AMP-dependent protein kinase regulatory su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 44 publications
1
51
0
Order By: Relevance
“…Activation of sAC would stimulate intramitochondrial protein kinase A (PKA) (Schwoch et al, 1990), which can phosphorylate many ETS proteins (Valsecchi et al, 2013), altering their activity (Lee et al, 2005;Tomitsuka et al, 2009;Phillips et al, 2012). Because sAC and PKA are temperature sensitive, such a mechanism could explain the pattern of mitochondrial suppression in hibernators, but to date no changes in the phosphorylation of mitochondrial proteins have been found among torpor bout phases, though seasonal differences are evident (Chung et al, 2013).…”
Section: A Role For Post-translational Modifications?mentioning
confidence: 99%
“…Activation of sAC would stimulate intramitochondrial protein kinase A (PKA) (Schwoch et al, 1990), which can phosphorylate many ETS proteins (Valsecchi et al, 2013), altering their activity (Lee et al, 2005;Tomitsuka et al, 2009;Phillips et al, 2012). Because sAC and PKA are temperature sensitive, such a mechanism could explain the pattern of mitochondrial suppression in hibernators, but to date no changes in the phosphorylation of mitochondrial proteins have been found among torpor bout phases, though seasonal differences are evident (Chung et al, 2013).…”
Section: A Role For Post-translational Modifications?mentioning
confidence: 99%
“…Evidence for the existence of a mtPKA in mammalian [16][17][18] and yeast mitochondria [19] has also been presented by' others. Among the various proteins found to be phosphorylated by the mtPKA, 42 kDa and 16-18 kDa pro-…”
Section: Chemicalsmentioning
confidence: 99%
“…In the IM fraction of bovine-heart mitochondria, consisting essentially of scrambled inner membrane, cAMP induces phosphorylation by [y-3ZP]ATP of proteins of apparent Mr 29,18 and 6 kDa ( Fig. 1) (see also [14,15]).…”
Section: *Corresponding Author Institute Of Medical Biochemistry Andmentioning
confidence: 99%
“…Recent work from our group has shown that in bovine heart mitochondria various proteins are phosphorylated by a cAMPdependent protein kinase (mtPKA) present in these organelles [7][8][9][10]. An mtPKA has also been detected in yeast mitochondria [1 1].…”
Section: Introductionmentioning
confidence: 99%